2011
DOI: 10.1007/s11240-011-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypocotyl derived in vitro regeneration of pumpkin ash (Fraxinus profunda)

Abstract: Pumpkin ash (Fraxinus profunda (Bush) Bush) is at risk for extirpation by an exotic insect, the emerald ash borer (EAB). Pumpkin ash is limited to wetland areas of the Eastern United States, and has been listed as an endangered species because of EAB activity. Pumpkin ash provides many benefits to the ecosystem, and its wood is used in the manufacturing industry. In vitro regeneration provides an integral tool for the mass propagation and genetic transformation of pumpkin ash to combat EAB. Therefore, a plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
4
7
0
Order By: Relevance
“…This is similar to Caesalpinia bonduc (Cheruvathur et al 2012), Carica papaya (Roy et al 2012), Santalum album (Singh et al 2013), Gardenia latifolia (Reddy and Saritha 2013), pumpkin ash (Stevens and Pijut 2012), date palm (Khan and Bi 2012), and Caesalpinia bonduc (Kumar et al 2012). All rooting percentages were at least 70%, and some reached 100%.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This is similar to Caesalpinia bonduc (Cheruvathur et al 2012), Carica papaya (Roy et al 2012), Santalum album (Singh et al 2013), Gardenia latifolia (Reddy and Saritha 2013), pumpkin ash (Stevens and Pijut 2012), date palm (Khan and Bi 2012), and Caesalpinia bonduc (Kumar et al 2012). All rooting percentages were at least 70%, and some reached 100%.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, we found that NAA in combination with the same concentrations of BA was superior to 2,4-D in terms of N. cadamba adventitious shoot formation. However, an over-abundance of BA, as for other cytokinins [thidiazuron (TDZ), zeatin or N 6 -(2-isopentenyl) adenine (2-ip)], may have negative effects in vitro on cotyledons, such as inhibition of shoot induction and propagation or hyperhydricity, and could limit adventitious shoot formation (Stevens and Pijut 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, callus occasionally appeared asynchronously on the hypocotyl explants that were exposed to 4.54 µM TDZ and above but was absent in all treatments containing adenine-type cytokinins. The occurrence of callusing on media incorporated with TDZ had been reported in other studies (Faisal and Anis 2005;Guo et al 2005;Sharma and Shahzad 2008;Stevens and Pijut 2012). Increasing the TDZ concentration to 4.54 µM and above significantly suppressed the regeneration capacity of the hypocotyl explants.…”
supporting
confidence: 75%
“…However, we found that BA concentrations higher than 2.0 mg · L -1 in combination with IAA had a negative effect on C. oleifera direct adventitious shoot formation (Table 1). This result was similar to those of previous studies on pumpkin ash (Huang et al, 2014;Stevens and Pijut, 2012). Therefore, the concentration of appropriate PGR was important for early establishment of shoot regeneration.…”
Section: Resultssupporting
confidence: 91%
“…Adventitious shoot organogenesis is an easy and fast plant regeneration method that can be induced via direct or indirect pathways. Hypocotyl explants have been used to achieve regenerated plants in many species including Fraxinus pennsylvanica (Du and Pijut, 2008), pumpkin ash (Fraxinus profunda) (Stevens and Pijut, 2012), carrot (Daucus carota) (Grzebelus et al, 2012), gherkin (Cucumis anguria L.) (Ju et al, 2014), Tamarillo (Cyphomandra betacea) (Kahia et al, 2015) and tung tree (Vernicia fordii) (Lin et al, 2016). However, little research has been conducted using radicles as explants for plant regeneration in C. oleifera.…”
mentioning
confidence: 99%